How Investor Structure Influences the Yield, Information Dissemination Efficiency, and Liquidity - Hongli Che; Xiong Xiong; Juntian Yang; Wei Zhang; Yongjie Zhang (Discrete Dynamics in Nature and Society)
This essay focuses on the investor structure of the stock index futures market and uses agent-based computational finance method to discuss how the volume-synchronized probability of informed trading (VPIN) affects market absolute yield, information dissemination efficiency, and liquidity with different ratios of informed traders in the market. The result shows that the higher the proportion of informed traders is, the more the volatility of the market is. Furthermore, the result indicates that when the proportion of informed traders in the stock index futures market accounts for 1/3-1/2, the transparency and liquidity of the market will be better.